Visualizing Head and Neck Tumors in Vivo Using Near-Infrared Fluorescent Transferrin Conjugate - Liang Shan; Yubin Hao; Songping Wang; Alexandru Korotcov; Renshu Zhang; Tongxin Wang; Joseph Califano; Xinbin Gu; Rajagopalan Sridhar; Zaver M. Bhujwalla; Paul C. Wang (Molecular Imaging)
Transferrin receptor (TfR) is overexpressed in human head and neck squamous cell carcinomas (HNSCCs). This study was carried out to investigate the feasibility of imaging HNSCC by targeting TfR using near-infrared fluorescent transferrin conjugate (Tf NIR ). Western blot analysis of four HNSCC cell lines revealed overexpression of TfR in all four lines compared with that in normal keratinocytes (OKFL). Immunocytochemistry further confirmed the expression of TfR and endocytosis of Tf NIR in JHU-013 culture cells. Following intravenous administration of Tf NIR (200 μL, 0.625 μg/μL), fluorescent signal was preferentially accumulated in JHU-013 tumor xenografts grown in the lower back ( n = 14) and oral base tissues ( n = 4) of nude mice. The signal in tumors was clearly detectable as early as 10 minutes and reached the maximum at 90 to 120 minutes postinjection. The background showed an increase, followed by a decrease at a much faster pace than tumor signal. A high fluorescent ratio of the tumor to muscle was obtained (from 1.42 to 4.15 among tumors), usually achieved within 6 hours, and correlated with the tumor size ( r = .74, p = .002). Our results indicate that TfR is a promising target and that Tf NIR -based optical imaging is potentially useful for noninvasive detection of early HNSCC in the clinic.